The impact of intradialytic exercise on immune cells expressing CCR5+ in patients with chronic kidney disease: A cross-over trial - Fuhro, Maria Isabel; Andrade, Francini P; Dorneles, Gilson P; Lira, Fabio S [UNESP]; Romão, Pedro RT; Peres, Alessandra; Monteiro, Mariane (SAGE Publications, 2021)
The C-C chemokine receptor type 5 (CCR5) plays a role in the immunopathogenesis of chronic kidney disease (CKD). Exercise has anti-inflammatory properties that may contribute to the rehabilitation of CKD patients. To date, the impact of the intradialytic exercise on CCR5 expression in monocytes and lymphocytes of CKD patients is unknown. We aimed to evaluate the effects of an acute intradialytic moderate-intensity exercise on CD4+CCR5+ T-cells and CD14+CCR5+ monocytes of elderly individuals with Chronic Kidney Disease (CKD). Eight CKD elderly patients performed a single bout of 20 min intradialytic exercise and a control hemodialysis (HD) session. Blood samples were collected at baseline, during and immediately after the trials. HD therapy increased the peripheral frequency of CD4+CCR5+ T-cells. The systemic CCL5 levels and the peripheral CD14+CCR5+ proportions increased during and after HD therapy. No significant alterations in CD4+CCR5+ and CD14+CCR5+ proportions or CCL5 levels were identified in CKD patients during and after intradialytic exercise. A negative correlation between the peripheral frequency of CD14+CCR5+ and the creatinine levels was identified in the intradialytic exercise session. A single moderate-intensity intradialytic exercise imposes an immunomodulatory impact in CKD elderly patients, preventing an excessive inflammatory response induced by hemodialysis.
Keywords: chemokine receptor; exercise; hemodialysis; inflammation; monocytes; Renal failure; T cells